The effects of teacher’ code-switching on students’ vocabulary acquisition: EFL learners - Via Rahma Wati; Muhammad Sofian Hadi (Journal of English Language and Pedagogy, 2021)
Abstract: English as Foreign Language (EFL) teaching and learning process, it is inevitable for teachers and students to be engaged in various cases involving L1 use. Code-switching has arisen a debatable notion of what it brings, good or bad, in the educational milieu. To some extent, it is believed that code-switching is such a help for both teachers and students in achieving the learning target while to some party the use of code-switching is no more than a hurdle. The classroom context in Indonesia where teachers and students share the same first language showed that CS was used by teachers in EFL classrooms. The research indicated that teachers used CS in the teaching and learning process for various reasons. The main reason would be to facilitate students’ learning, besides that code-switching also has an effect on students vocabulary acquisition in L2. Keywords: code-switching, the effect of teacher’s code-switching, vocabulary.